2001
DOI: 10.1902/jop.2000.72.9.1241
|View full text |Cite
|
Sign up to set email alerts
|

Local Versus Systemic Adjunctive Antibiotic Therapy in 28 Patients With Generalized Aggressive Periodontitis

Abstract: These results indicate that the local delivery of tetracycline by a fiber or the systemic administration of amoxicillin/clavulanic acid given 3 months after scaling and root planing produced similar clinical outcomes over the 9-month observation period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
1
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 29 publications
2
46
1
1
Order By: Relevance
“…However, no significant difference was found between systemic and local administrations of the drugs when combined with SRP, indicating the stronger effect of mechanical periodontal treatment on clinical healing. To date, 4 studies have compared the efficacy of local drug delivery and administration of systemic antibiotics (56)(57)(58)(59). In one of these studies, no significant difference was found between treatments with respect to probing depth reduction and increase of clinical attachment (58).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, no significant difference was found between systemic and local administrations of the drugs when combined with SRP, indicating the stronger effect of mechanical periodontal treatment on clinical healing. To date, 4 studies have compared the efficacy of local drug delivery and administration of systemic antibiotics (56)(57)(58)(59). In one of these studies, no significant difference was found between treatments with respect to probing depth reduction and increase of clinical attachment (58).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, others found that there was no difference in clinical results when application of local metronidazole was compared to systemic metronidazole (56). Purucker et al (59) have compared the clinical effects of systemic amoxicillin/clavulanic acid treatment versus local tetracycline therapy 3 months after SRP treatment and concluded that the local delivery of tetracycline by a fiber or the systemic administration of amoxicillin/clavulanic acid produced similar clinical outcomes. However, similar to our findings, in another study local metronidazole provided better results than systemic metronidazole with regard to bone deposition when assessed by subtraction radiography (57).…”
Section: Discussionmentioning
confidence: 99%
“…Adjunctive use of LDD agents like controlled release biodegradable chlorhexidine gluconate chip [61, 62], tetracycline fibers [63, 64], and minocycline-Hcl gel [65] has been tried in aggressive periodontitis with superior clinical outcomes. The decision to use local anti-infective adjunctive therapy remains a matter of individual clinical judgment, the phase of treatment, and the patient's status and preferences.…”
Section: Discussionmentioning
confidence: 99%
“…The use of local delivery of antimicrobial agents to the management of localized aggressive periodontitis is effective when does not respond adequately to mechanical and systemic antibiotic therapy. Adjunctive use of local drugs delivery agents like controlled release biodegradable chlorhexidine gluconate chip, tetracycline fibers and minocycline-HCl gel has been tried in aggressive periodontitis with superior clinical outcomes [69][70][71][72][73] .…”
Section: Serial and Combination Therapymentioning
confidence: 99%